IMPLEMENTASI PENDEKATAN TAKTIK DALAM PEMBELAJARAN INVASION GAMES DI SEKOLAH DASAR - Yudanto Yudanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
Games are one of the physical education contents. Invasion games such as soccer-like and basketball- like games are the materials taught at elementary level. The learning process of invasion games can be done through various approaches. Tactical approach is one of approaches in teaching invasion games. Tactical approach is an approach emphasizing on the games and skill learning in game situation. Tactical awareness and problem solving in the games is the key in the tactical approach. The steps in invasion games teaching using the tactical approach are; (1) game form, (2) tactical awareness (what to do), (3) skill execution (how to do). Teaching invasion games need to be based in the framework and the levels of complexities of the games which have previously been determined. Games learning through tactical approach encourage and demand students to solve tactical problems in the games. Kata Kunci: Pendekatan Taktik, Pembelajaran Invasion Games, Sekolah Dasar.